The Enhancement of Students Mathematical Communication Ability Through RME-Textbook - Rahmawati Suwanto, Fevi; Wijaya, Ariyadi (SJME (Supremum Journal of Mathematics Education), 2021)
This study was a research and development used ADDIE model aimed to produce mathematics textbook for 8th-grade students by applying five principles of the Realistic Mathematics Education (RME) approach, included: phenomenological exploration, bridging by vertical instruments, self-reliance with students own constructions and productions, interactivity, and intertwining. The subject in this study involved 30 students' junior high school in Yogyakarta. The qualities of the developed textbook refer to three criteria, namely validity, practicality, and effectiveness. Supporting instruments used to examine three criteria for the quality of the textbook were validation sheets, assessment sheets for teachers and students, and students' mathematical communication ability test. The textbook meets the criteria of validity, practicality, and effectiveness if at least "good" from the results of validator assessments, the results analysis from teachers and student assessments, and at least 75% of the students' mathematical communication ability test results. Based on the results of this study, the developed textbook has met the criteria of validity (very good), practicality (very good by the teacher and good by students), and effectiveness (good for 86.67%). Therefore, developing textbooks is suitable to use as an alternative to enhance the students' mathematical communication ability.